The food of life: an evaluation of the impact of cash grant receipt and good parenting on child nutrition outcomes in South Africa and Malawi. (December 2020) - Sherr, Lorraine; Roberts, Kathryn J.; Mebrahtu, Helen; Tomlinson, Mark; Skeen, Sarah; Cluver, Lucie D.
Social protection interventions (inclusive of cash grant receipt and care provision) have been found to be effective in response to some of the negative implications of the HIV epidemic on children and families. This study explores the impact of cash grant receipt and care provision (operationalised as good parenting) on child nutritional outcomes. In this cross-sectional study, 854 children and younger adolescents (5–15 years) and caregivers affected by HIV, attending community-based organisations in South Africa and Malawi, were interviewed. Interviews comprised inventories on socio-demographic information, family data, cash grant receipt and child nutrition. Parenting was measured using a composite scale. Logistic regression and marginal effects analyses were used to explore the associations between differing levels of social protection (none; either cash or good parenting; cash and good parenting) and child nutritional outcomes. One hundred and sixty children (20.3%) received neither cash nor good parenting; 501 (63.5%) received either cash or good parenting and 128 (16.2%) received both cash and good parenting. In comparison to no intervention, receipt of either cash or good parenting was significantly associated with child non-stunting, the child having sufficient food, and the child not looking thin. Three (3/7) nutritional outcomes showed increased improvement amongst children receiving both cash and good parenting care including child-reported non-hunger, child non-stunting and parental report of sufficient food. Marginal effects analyses further identified an additive effect of cash and good parenting on child nutritional outcomes. This study indicates that receipt of combined cash and good parenting, when compared to cash grant receipt alone, has positive effects on nutrition-related child outcomes.